Development of Practice Guidelines for the Prevention and Treatment of Postpartum Hemorrhage in Mothers with Normal Labor at Narathiwas Rajanagarindra Hospital - Rothmanee, Penkae; Kumpasano, Thitirat; Masaesaai, Sameenee (Princess of Naradhiwas University Journal, 2025)
This research and development aimed to develop practice guidelines for the prevention and treatment of postpartum hemorrhage (PT-PPH) in mothers with normal labor and evaluate the effectiveness and satisfaction with the use of PT-PPH. The sample group consisted of 74 multidisciplinary obstetrics team members and 300 mothers with normal labor at Narathiwas Rajanagarindra Hospital. Research instruments included 1) a postpartum Hemorrhage (PPH) situation analysis form; 2) maternal data; 3) an AGREE II 2017 assessment form; 4) a PT-PPH usage checklist; and 5) satisfaction with the use of the PT-PPH practice guideline using the Likert Scale and Visual Analog Scale (VAS). Content validity of instrument number 3, 4, and 5 was tested by experts. Reliability of set 3 was .983, set 4 was .75, and set 5 of satisfaction with the Likert Scale = .915; VAS = .998. Situation data was analyzed by using the Colaizzi Technique. Other data were analyzed by using descriptive statistics and an F-test. Results revealed that the interdisciplinary team jointly developed and designed the PT-PPH draft, dividing it into prevention groups: low-risk PPH and high-risk PPH. The treatment group included impending PPH, PPH, and severe PPH with shock. The researchers designed the PT-PPH form with 3 columns on a single sheet that included 1) "condition" characteristics of the risk group; 2) “order for one day”; 3) “order for continuation” that clearly separate the treatment plans for each group. The treatment results according to PT-PPH in the first 150 cases showed 2 instances of postpartum hemorrhage due to non-compliance with PT-PPH. The researchers adjusted PT-PPH to make it more user-friendly. In the subsequent 150 cases, no instances of postpartum hemorrhage were observed. The average satisfaction scores for the use of PT-PPH in all groups were at a high level. The results of this study will serve as data for the further development of the PPH prevention and treatment system.